2020
DOI: 10.1002/pen.25346
|View full text |Cite
|
Sign up to set email alerts
|

Form‐Stabilized Polyethylene Glycol/Palygorskite Composite Phase Change Material: Thermal Energy Storage Properties, Cycling Stability, and Thermal Durability

Abstract: In this work, polyethylene glycol (PEG) as a phase change material (PCM) was incorporated with palygorskite (Pal) clay to develop a novel form‐stable composite PCM (F‐SCPCM). The Pal/PEG(40 wt%) composite was defined as F‐SCPCM and characterized using SEM/EDS, FT‐IR, XRD, DSC, and TGA techniques. The DSC results revealed that the F‐SCPCM has a melting temperature of 32.5°C and latent heat capacity of 64.3 J/g for thermal energy storage (TES) applications. Thermal cycling test showed that the F‐SCPCM had good c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…6,7 The first problem can be overcome via shape stabilization of PCMs. In this context, several porous supporter materials have been handled for easy and cheap production of shape-stable composites, some of which are attapulgite, 8,9 diatomite, 10−12 natural clay, 13 perlite, 14−16 silica fume, 17,18 vermiculite, 19−22 and bentonite. 23,24 On the other hand, fly ash (FA) composed of mainly silica and alumina is a good candidate for the production of shape-stabilized composite PCMs (SSC-PCMs) as a lightweight supporter porous material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 The first problem can be overcome via shape stabilization of PCMs. In this context, several porous supporter materials have been handled for easy and cheap production of shape-stable composites, some of which are attapulgite, 8,9 diatomite, 10−12 natural clay, 13 perlite, 14−16 silica fume, 17,18 vermiculite, 19−22 and bentonite. 23,24 On the other hand, fly ash (FA) composed of mainly silica and alumina is a good candidate for the production of shape-stabilized composite PCMs (SSC-PCMs) as a lightweight supporter porous material.…”
Section: Introductionmentioning
confidence: 99%
“…are the pioneer materials because of some of their superior properties such as high LHTES properties, cycling stability, nontoxicity, negligible super cooling, and low vapour pressure. Still, the leakage issue which emerged throughout the solid–liquid phase transition and low thermal conductivity are the most important deficiencies that restrict their usage in passive solar TES activites. , The first problem can be overcome via shape stabilization of PCMs. In this context, several porous supporter materials have been handled for easy and cheap production of shape-stable composites, some of which are attapulgite, , diatomite, natural clay, perlite, silica fume, , vermiculite, and bentonite. , On the other hand, fly ash (FA) composed of mainly silica and alumina is a good candidate for the production of shape-stabilized composite PCMs (SSC-PCMs) as a lightweight supporter porous material. FA is a byproduct obtained from coal-fired power generation plants and its treatment and comprehensive utilization has been one of the hot social topics among researchers.…”
Section: Introductionmentioning
confidence: 99%
“…[30,31] A variety of ssPCMs using PEG as phase change ingredient have been reported. Sarı et al reported a series of PEG based ssPCMs using different inorganic materials (gypsum and natural clay, [32] diatomite/CNTs, [33] and palygorskite [34] ) as supports, and the heat storage density of the ssPCMs is in the range of 24.18-64.3 J/g. PEG based ssPCMs with higher latent heat were obtained using polymers as supporting materials for encapsulating PEG.…”
Section: Introductionmentioning
confidence: 99%
“…Form‐stable PCMs composed of working media and skeletal substances can effectively prevent the leakage, which can maintain the solid state even if the phase of the working media turned from solid to liquid at the temperature higher than the melting temperature of working media. Various supporting matrix, including inorganic porous materials such as expanded graphite (EG), [ 31–33 ] activated carbon (AC), [ 34,35 ] mineral, [ 36–39 ] and polymers, [ 40–44 ] have been used as form‐stabilization substances. Compared with inorganic porous matrix, the polymers have relative higher mechanical strength and toughness.…”
Section: Introductionmentioning
confidence: 99%